In vivo confocal microscopy of early corneal epithelial recovery in patients with chemical injury - Xiang, J (Eye (Lond), 2015)
PURPOSE: To investigate the early recovery of corneal epithelium in patients with chemical injuries by the application of in vivo laser scanning confocal microscopy (LSCM). METHODS: LSCM was performed on 26 eyes of 18 consecutive patients at 1, 2, and 3 months post injury. The morphology of central corneal epithelium and limbus was evaluated. Analysis was performed to compare the densities of corneal apical surface cells (ASCs) and basal epithelial cells (BECs) among different injury severity and time points after injury. The comparisons were also made on inflammatory cells (ICs) and dendritic cells (DCs) infiltrating at the limbus. Moreover, the presence rate of palisades of Vogt (POV) was analyzed at 3 months post injury. RESULTS: Corneal re-epithelialization was found within 3 months post injury in all eyes, except that persistent epithelium defect was identified in grade IV injured eyes even at 3 months after injury. The injury severity had a significantly negative correlation with the densities of ASCs. However, it had no relationship with the densities of BECs. The density of ICs at the limbus decreased significantly with the prolongation of follow-up, except in the grade I injured eyes. The presence rate of POV also had a significantly negative correlation with injury severity. CONCLUSION: Epithelial recovery after chemical injury varied in cellular morphology and the densities of ASCs among eyes with different injury severity. The presence rates of POV decreased with the aggravation of injury. LSCM is a feasible method for observing the early recovery of corneal epithelium in patients with chemical injuries.